High fat diet increases the severity of collagen-induced arthritis in mice by altering the gut microbial community - Yang Zhang; Jie Zhang; Yantong Liu; Shuang Ren; Ning Tao; Fanyan Meng; Qi Cao; Ruoshi Liu (Advances in Rheumatology, 2024)
Abstract Objectives Research has demonstrated that obesity may be associated with rheumatoid arthritis (RA). In addition, gut microbiota and its metabolites contribute to the occurrence and development of RA and obesity. However, the mechanism by which obesity affects RA remains unclear. In this study, we aimed to investigate whether gut microbiota and their metabolites alter the effects of high fat diet (HFD) on the severity of collagen-induced arthritis (CIA) in mice. Methods Briefly, mice were divided into normal group (N), CIA model group (C), HFD group (T), and HFD CIA group (CT). Hematoxylin and Eosin staining(HE) and Safranin O-fast green staining were conducted, and levels of blood lipid and inflammatory cytokines were measured. 16S rDNA sequencing technique and liquid chromatography-mass spectrometry (LC-MS)-based metabolomics were performed to explore changes in the microbiota structure to further reveal the pathomechanism of HFD on CIA. Results HFD aggravated the severity of CIA in mice. The CT group had the highest proportion of microbial abundance of Blautia, Oscillibacter, Ruminiclostridium-9, and Lachnospiraceae UCG 006 at the genus level, but had a lower proportion of Alistipes. Additionally, the fecal metabolic phenotype of the combined CT group shows significant changes, with differential metabolites enriched in 9 metabolic pathways, including primary bile acid biosynthesis, arginine biosynthesis, sphingolipid metabolism, purine metabolism, linoleic acid metabolism, oxytocin signaling pathway, aminoacyl-tRNA biosynthesis, the pentose phosphate pathway, and sphingolipid signaling pathway. Correlation analysis revealed that some of the altered gut microbiota genera were strongly correlated with changes in fecal metabolites, total cholesterol (TC), triglyceride (TG), and inflammatory cytokine levels. Conclusions This study shows that HFD may aggravate inflammatory reaction in CIA mice by altering the gut microbiota and metabolic pathways.